Tafasitamab and Lenalidomide as Second-Line Treatment in an Elderly Patient with a Primary Refractory Double-Hit Diffuse Large B-Cell Lymphoma - Alexander Meisel; Ziad Kassem; Daniel Turek; Tanja Angelina Gradistanac; Tristan de Lage; Christina Züger (healthbook TIMES. Oncology Hematology)
The phase II L-MIND study demonstrated that treatment with tafasitamab in combination with lenalidomide yielded high complete response rates in patients with relapsed or refractory diffuse large B-cell lymphoma (DLBCL). Patients with primary refractory DLBCL relapsing within three months of frontline therapy (later amended to six months) and double-hit lymphoma were excluded. In this case report, we present the clinical course of an 85-year-old woman with primary refractory, double-hit DLBCL who was successfully treated with tafasitamab plus lenalidomide following disease progression on the R-mini-CHOP regimen.